2022
DOI: 10.1039/d1gc03646g
|View full text |Cite
|
Sign up to set email alerts
|

Facile formation of black titania films using an atmospheric-pressure plasma jet

Abstract: A rapid atmospheric-pressure pulsed helium/hydrogen plasma jet method for conversion of TiO2 films into defective, black TiO2 is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Hence, obtaining strong light absorption in ultrathin semiconductors has been of great scientific and technological interest for many years, making it one of the essential aspects for the efficient generation of photocarriers, as well as the development of ultrafast optoelectronic devices and surface-active photocatalysts. , However, ultrathin films of many naturally occurring semiconductor materials provide only limited freedom for controlling the spectral location and magnitude of light absorption, since their intrinsic optical properties are fixed . In contrast, ultrathin metasurfaces constructed from two-dimensional subwavelength arrays of semiconductor structures have shown tremendous potential for concentrating and controlling light on the nanoscale, positioning them as an ideal toolkit for engineering the light absorption in catalytic materials. Indeed, recent examples have shown that such artificial materials can increase the internal quantum efficiency of semiconductors and metals when shaping them into catalytic metasurfaces. , …”
mentioning
confidence: 99%
“…Hence, obtaining strong light absorption in ultrathin semiconductors has been of great scientific and technological interest for many years, making it one of the essential aspects for the efficient generation of photocarriers, as well as the development of ultrafast optoelectronic devices and surface-active photocatalysts. , However, ultrathin films of many naturally occurring semiconductor materials provide only limited freedom for controlling the spectral location and magnitude of light absorption, since their intrinsic optical properties are fixed . In contrast, ultrathin metasurfaces constructed from two-dimensional subwavelength arrays of semiconductor structures have shown tremendous potential for concentrating and controlling light on the nanoscale, positioning them as an ideal toolkit for engineering the light absorption in catalytic materials. Indeed, recent examples have shown that such artificial materials can increase the internal quantum efficiency of semiconductors and metals when shaping them into catalytic metasurfaces. , …”
mentioning
confidence: 99%
“…In addition, the weak absorption in the 400-500 nm visible region can be attributed to the sub-band-gap light absorption caused by the oxygen vacancies at the band tail. 31 Fig. 3b shows a schematic diagram of the vertical structure of the STO/TiO 2 device, with FTO and In as the bottom electrode and top electrode, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the weak absorption in the 400–500 nm visible region can be attributed to the sub-band-gap light absorption caused by the oxygen vacancies at the band tail. 31…”
Section: Resultsmentioning
confidence: 99%
“…However, the process needs a vacuum chamber and pump, with expensive costs and complicated operation. Atmospheric pressure (AP) plasma has also been used to prepare black TiO 2 and has shown high hydrogenation efficiency, reducing equipment and handling costs [25]. In our previous work [26], TiO 2 coated on Ni foam was successfully hydrogenated by RF AP He/H 2 plasma within a short time (5 min).…”
Section: Introductionmentioning
confidence: 99%